The prevalence of diabetic peripheral neuropathy in youth with diabetes mellitus - Piengjai Sophausvaporn; Jariya Boonhong; Taninee Sahakitrungruang (Korean Society of Pediatric Endocrinology, 2023)
Purpose Diabetic neuropathy (DN) is a serious complication in diabetes mellitus. We aimed to determine the prevalence of DN in pediatric-onset diabetes in a tertiary care center and to assess the sensitivity and specificity of monofilament testing and noninvasive screening to diagnose DN compared with the gold standard nerve conduction study (NCS). Methods Sixty-five Thai children and adolescents (39 females) diagnosed with diabetes before 15 years of age were included. All subjects were screened for DN by foot and neurological examinations, light touch sensation by 10 g Semmes-Weinstein monofilaments, and the Michigan Neuropathy Screening Instrument (MNSI). NCSs were used as the gold standard for diagnosis of DN. Results Fifty-eight patients had type 1 diabetes (T1D), 5 patients had type 2 diabetes, and 2 patients had other types of diabetes. The mean age was 17.7±4.6 years (8-33 years). The prevalence of DN in this cohort was 12.3% by NCS. All subjects were asymptomatic. Mean diabetes duration did not differ between the groups (with DN 8.0±3.0 years vs. no DN 8.2±5.0 years). Notably, one patient with T1D developed DN within 3 years after diagnosis. Poor glycemic control was a significant risk factor for DN. Glycosylated hemoglobin was higher in the DN group (10.6%±2.3% vs. 8.5%±1.6%, P=0.008). The occurrence of diabetic nephropathy was associated with DN (prevalence rate ratio, 4.97; 95% confidence interval, 1.5-16.46). Foot and neurological examinations, monofilaments, and the MNSI failed to detect DN in all subjects with abnormal NCS. Conclusions The prevalence of DN in pediatric-onset diabetes is not uncommon but mainly is subclinical. Poor glycemic control is the main risk factor. Noninvasive screening tests for DN exhibited poor diagnostic sensitivity in the pediatric population.